2021
DOI: 10.4269/ajtmh.20-1302
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Impaired Mental Health among Medical Students during the Early Stage of the COVID-19 Pandemic in Morocco

Abstract: The COVID-19 pandemic has great consequences on mental health. We aimed to assess medical students’ psychological condition and influencing factors as a baseline evidence for interventions promoting their mental wellbeing. We conducted an online survey from April 8 to April 18, 2020 to examine the mental health of medical students by the nine-item Patient Health Questionnaire, seven-item Generalized Anxiety Disorder Scale, seven-item Insomnia Severity Index, and six-item Kessler psychological distress scale. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
78
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 40 publications
9
78
0
7
Order By: Relevance
“…The highest number of students (92.3%) were suffering from depression of various severity, mostly minimum to mild (58.5%) compared to other common psychiatric illnesses, including anxiety, OCD, and PTSD. This finding is similar to a recent study [ 23 ] conducted in Morocco using the same measuring tools for depression and anxiety and revealing that among all the common psychiatric illnesses, depression was more common than the others. In their study with a sample of 549 medical students, 410 (74.6%) reported depression while 341 (62.3%) had anxiety, 344 (62.6%) insomnia, and 379 (69%) distress.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The highest number of students (92.3%) were suffering from depression of various severity, mostly minimum to mild (58.5%) compared to other common psychiatric illnesses, including anxiety, OCD, and PTSD. This finding is similar to a recent study [ 23 ] conducted in Morocco using the same measuring tools for depression and anxiety and revealing that among all the common psychiatric illnesses, depression was more common than the others. In their study with a sample of 549 medical students, 410 (74.6%) reported depression while 341 (62.3%) had anxiety, 344 (62.6%) insomnia, and 379 (69%) distress.…”
Section: Discussionsupporting
confidence: 91%
“…The study shows a very high proportion (93.1%) of undergraduate and postgraduate medical students having some degree of psychological problem while only 17% of them had any history of psychiatric illness in the pre-pandemic period; this assault on psychiatric wellbeing during the pandemic period is in accord with studies on medical students in Pakistan [ 19 ], UK [ 20 ], Japan [ 21 ], India [ 22 ], Morocco [ 23 ] and nursing students in Indonesia [ 18 ]. Also, several studies reflect increased stress, anxiety, and depression as an influence of the COVID-19 epidemic among all strata of society, including the general public [ 5 , 6 , 17 ], health care workers [ 3 , 8 ], older adults [ 24 ] and students of all categories [ 25 ], In contrast, a study from Iran [ 26 ] shows only 27.6% of medical students having depression.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In their BEME Guide to developments in response to the COVID-19 pandemic, Daniel et al identified several publications, but only three focussing on wellbeing in undergraduate medical education [2]. The comprehensive measures of social distancing with school and university closures, restricted social connections, and loss of routine potentially have a huge negative effect on individuals' social networks [9] and mental wellbeing [9][10][11][12][13][14][15][16][17][18][19][20] although risk factors in principle remain the same: low income, living alone, younger age, female gender, and pre-existing mental health conditions [12,13,15,21]. Thus, in addition to examining the primary impact of COVID-19, a second focus of research is needed to not only map but to explain the impact of secondary measures such as the fundamental shift of faculties to replacing or supplementing on-site teaching with e-learning on students' learning and mental wellbeing.…”
Section: Introductionmentioning
confidence: 99%